Advanced NGS analysis of cell-free tumor DNA supports clonal relation to primary high-grade B-cell lymphoma lesion and CNS relapse despite MRI negativity - Veronika Navrkalova; Andrea Mareckova; Jakub Porc; Samuel Hricko; Viera Hrabcakova; Jarmila Kissova; Sona Kundova; Marie Jarosova; Sarka Pospisilova; Jana Kotaskova; Andrea Janikova (Diagnostic Pathology)
Abstract High-grade B-cell lymphomas (HGBCLs) are aggressive blood cancers with a severe disease course, especially when the central nervous system (CNS) is involved. Standard histological examination depends on tissue availability and is currently supplemented with molecular tests, as the status of MYC, BCL2, or BCL6 gene rearrangements is required for proper lymphoma classification. This case report demonstrates the relevance of cerebrospinal fluid (CSF) cell-free DNA testing by integrative next-generation sequencing (NGS) panel. The benefit of this approach resided in tumor genotyping alongside the proof of CNS progression despite MRI negativity, revealing a clonal relationship with the primary tumor lesion. In addition, our strategy allowed us to classify the tumor as DLBCL/HGBL-MYC/BCL2 entity. In clinical practice, such a minimally invasive approach provides a more sensitive tool than standard imaging and cell analyzing techniques, enabling more accurate disease monitoring and relapse prediction in particular cases.